Production and nutritional value of Mombaça grass with application of whey as an alternative nitrogen source - Mantovani, José Ricardo (2022)
Whey is a waste generated in large quantities in dairy industries, and its use in agriculture as a source of nutrients can be an appropriate destination. Thus, the objective of this study was to evaluate the effect of whey as a nitrogen source for production and nutritional value of Mombaça grass. The experiment was conducted in pots, in a randomized blocks factorial scheme with four replicates. The treatments consisted of 5 doses of whey (0; 100; 200; 300 and 400 mg dm-3 N) associated with 3 doses de N-urea (0; 100 and 200 mg dm-3 N). Portions of 7 dm3 soil were incubated with lime and phosphate fertilizer and, 15 days before the end of incubation, the doses of whey were applied. After incubation, sowing followed by thinning (four plants/pot) were carried out, and the doses of N-urea were divided into 3 applications. Three grass cuts were made and, after the first cut, the treatments doses of whey and N-urea were reapplied. Whey fertilization increased the number of tillers, shoot dry matter production and crude protein of Mombaça grass, and the increases obtained varied as a funcion of the grass cycle and the N-ureea dose. The agronomic efficiency index of whey with N source in relation to urea was, on average, 69%. The whey increases production and improves the nutritional value of Mombaça grass, being an efficient alternative source of N for the forage.